1997
DOI: 10.1103/physrevb.55.9534
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced anomalous heat generation in AgCl and AgBr single crystals at liquid-helium temperature

Abstract: Anomalous heat generation induced by band-gap light illumination was observed in AgCl and AgBr single crystals by a sensitive photocalorimetric method at liquid-helium temperature. The generated heat per second was estimated to be one to two orders of magnitude larger than the absorbed energy per second. This heat generation lasted for more than 10 h after termination of the band-gap light illumination, indicating that exothermic chain reactions were triggered by the absorbed photons. In a crystal which was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…PCS is a kind of photothermal spectroscopy, measuring the heating of a sample under illumination, due to non-radiative processes of excited carriers [2]. The details of the arrangement of PCS measurement were as stated elsewhere [3].…”
Section: Methodsmentioning
confidence: 99%
“…PCS is a kind of photothermal spectroscopy, measuring the heating of a sample under illumination, due to non-radiative processes of excited carriers [2]. The details of the arrangement of PCS measurement were as stated elsewhere [3].…”
Section: Methodsmentioning
confidence: 99%
“…The increased density of SEC has been suggested by another experiment. Kondo et al repoted that the silver halide crystals subjected to the band-gap light show temperature rise as if heat is generated in the crystals and that plastic deformation of the samples strongly enhanced the temperature rise [7]. Later, they found that the temperature rise is due to the absorption of black-body radiation by the SEC by following measurements.…”
Section: Introductionmentioning
confidence: 99%